2015
DOI: 10.1377/hlthaff.2014.0986
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Surgery For Kidney Cancer Increased Access To A Procedure That Can Reduce Mortality And Renal Failure

Abstract: Surgeons increasingly use robot-assisted minimally invasive surgery for a variety of medical conditions. For hospitals, the acquisition and maintenance of a robot requires a significant investment, but financial returns are not linked to any improvement in long-term patient outcomes in the current reimbursement environment. Kidney cancer provides a useful case study for evaluating the long-term value that this innovation can provide. Kidney cancer is generally treated through partial or radical nephrectomy, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We found an association between higher LRN use in patients who reside in areas with a higher number of surgeons in bivariate analysis; although, this association was attenuated after adjusting for effects of other characteristics. While similar studies have reported associations between surgical trends in RCC and other health care system or provider variables (e.g., hospital, geographic region, resources within a hospital referral regions, surgery volume, physician specialty) 8,28 , our study is among the first to assess the impact of number of surgeons on LRN use.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We found an association between higher LRN use in patients who reside in areas with a higher number of surgeons in bivariate analysis; although, this association was attenuated after adjusting for effects of other characteristics. While similar studies have reported associations between surgical trends in RCC and other health care system or provider variables (e.g., hospital, geographic region, resources within a hospital referral regions, surgery volume, physician specialty) 8,28 , our study is among the first to assess the impact of number of surgeons on LRN use.…”
Section: Discussionmentioning
confidence: 90%
“…These findings add to those from prior studies 25,26 , including an analysis using SEER-Medicare data that showed increasing use of LPN among RCC patients with tumors ≤7cm, between 1995 and 2007. Some studies suggest such growth in LPN use over time may be due, in part, to the increased use of robot-assisted LPN (RALPN) for localized tumors 27,28 . A study by Patel et al 27 of patients who underwent RN, PN, or renal ablation in the state of Maryland from 2000 to 2011, found that the increase in PN use over the study period (of 18%) was largely driven by RALPN, accounting for nearly 66% of the rise in PN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11] Since the introduction and dissemination of robotic technology, the utilization of MIPN has surpassed OPN as the most common approach for PN. [12][13][14][15] However, contemporary data assessing the perioperative morbidity of OPN and MIPN are limited. Early reports describing improved perioperative outcomes with MIPN were largely limited to single institution cohorts with small sample sizes.…”
mentioning
confidence: 99%
“…While focusing on a limited number of cancers affects the generalizability of our findings, the cancers considered in this study cover about 85% of all incident cancer cases 39 . Second, new treatment interventions were limited to cancer pharmaceutical interventions and did not account for non-pharmaceutical innovations, such as robotic surgery, advances in radiotherapy and other surgical techniques, which may also affect cancer mortality 80 . However, this is unlikely to affect our estimates of the association of drug innovation with cancer mortality for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%